Increasing Student Participation to Tasks In Theme 4 in Learning Type Through Stad Type Cooperative Learning Model In SDN 2 Petahunan - Sri Setyaningsih (Universitas Sebelas Maret, 2020)
This study aims to increase learning participation through themethod STAD Cooperative Learning in grade 1 at SD Negeri 2 Petahunan. This type of research is classroom action research (PTK). The research subjects were 8 grade students of SD Negeri 2 Petahunan, consisting of 5 male students and 3 female students. The data collection technique used observation sheets, questionnaires. The research data were analyzed descriptively qualitatively. The results of this study indicate that the application of themethod stad type of cooperative learning in learning activities can increase student participation in group learning activities. For the score in cycle I, attendance participation has a percentage of 63%, asking 37%, opinion 25%, presentation readiness 25%, In the action stage of cycle II, the percentage of each aspect has increased to attendance participation has a percentage of 100%, asking 75 %, think 75%, presentation readiness 75% In the action stage of cycle III, the percentage of each aspect has increased to attendance participation has a percentage of 100%, ask 100%, think 100%, presentation readiness 87% From the data acquisition, themethod is applied. cooperativeLearning STAD in online thematic learning can increase student participation in learning activities / group discussions in grade 1 SD Negeri 2 Petahunan.